Extraterritorial trade sanctions: Theory and application to the US–Iran–EU conflict - Eckhard Janeba (Review of International Economics, 2023)
Under extraterritorial sanctions the sanctioning country extends its policies to trade of third countries with the sanctioned country. An example is President Trump's decision in 2018 to leave the Joint Comprehensive Plan of Action (JCPOA), a multilateral agreement with Iran. In this article, I develop a game-theoretic model to explain the emergence of extraterritorial sanctions. Such trade sanctions (i) do not arise when the harmful activity of the sanctioned country (“build a nuclear bomb”) is verifiable even if monetary transfers are ruled out, but (ii) emerge if a second activity (“sponsor international terrorism”) is not verifiable, and the sanctioning countries differ in their gains from trade with the sanctioned country, their harm from the non-verifiable activity, and their cost from abandoning the international economic order. In the context of the US–Iran–EU conflict, I argue that the oil and gas fracking boom in the US together with former President Trump's ignorance of his international reputation are key factors in the emergence of extraterritorial trade sanctions.
Keywords: 330; extraterritorial sanctions; international trade; sanctions; US–Iran conflict